Urinary Claudin-2 Measurements as a Predictor of Necrotizing Enterocolitis: A Pilot Study - Brian P Blackwood; Douglas R Wood; Carrie Y Yuan; Joseph D Nicolas; Anne Griffiths; Karen Mestan; Catherine J Hunter (EL-Med-Pub, 2015)
Background: Necrotizing Enterocolitis (NEC) affects 5-10% of NICU patients where initially patients may have only nonspecific clinical findings. A noninvasive tool for detection would aid in diagnosis. Increased urinary claudins have been associated with active adult inflammatory bowel disease. Methods: Institutional Review Board approval was obtained. Neonatal intestinal tissue samples were obtained from patients with and without NEC. Immunofluorescence analysis of claudin-2 was performed on the intestinal tissue. Thirty two urine samples were collected from 6 NICU patients. Proteins were extracted and urinary claudin-2 expression was measured using Western Blot Analysis. All sample concentrations were normalized to urinary creatinine. Differences were analyzed with ANOVA or Student's T-test. Findings were correlated to the patient's clinical status. Results: Neonatal intestinal immunofluorescence analysis revealed that claudin-2 is present in healthy intestinal epithelium and is decreased in NEC intestinal tissue (p=0.0001). Of the six patients evaluated, three patients had NEC. All 3 patients with NEC had spikes in urinary claudin-2 levels (p<0.001, p<0.001, p 0.0598 respectively). Spikes did not appear to correlate with other etiologies of neonatal sepsis, medication use or need for mechanical ventilation. Levels during active NEC were almost twice that of NEC-free periods (p<0.0001). Conclusion: A tool for early detection would facilitate early intervention and potential prevention of severe NEC. Preliminary findings indicate that urinary claudin-2 may represent a potential biomarker for NEC worth further investigation.